2017
DOI: 10.5400/jts.2017.v22i2.87-95
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Coal Bottom Ash and Cattle Manure as Soil Ameliorant on Acid Soil and Its Effect on Heavy Metal Content in Mustard (Brassica juncea)

Abstract: Coal bottom ash and cattle manure can be used as soil ameliorant. The application of coal bottom ash and cattle manure can improve the soil chemical properties, such as pH and the amounts of available nutrients in soil. The objective of the study was to understand the effect of coal bottom ash and cow manure application on soil chemical properties and heavy metal contents in soil and mustard (Brassica juncea).  A pot experiment was conducted in a greenhouse, including three treatment factors, i.e. age of coal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Abu terbang dan abu dasar dapat juga meningkatkan muatan negatif melalui proses deprotonasi ion H + (Priatmadi et al, 2014), dan karekteristik limbah abu batu bara dapat digunakan sebagai penetral pH tanah dan menurunkan keasaman tanah (Hermawan et al, 2014). Abu dasar dapat meningkatkan kapasitas tukar kation, sehingga digunakan sebagai amelioran yang tidak merusak struktur tanah, tanaman, lingkungan, meningkatkan kesediaan hara, dan sumber energi mikroorganisme (Agustini et al, 2017).…”
Section: Gambar 5 Berat Basah (Gram) Tanaman Tomat 90 Hstunclassified
“…Abu terbang dan abu dasar dapat juga meningkatkan muatan negatif melalui proses deprotonasi ion H + (Priatmadi et al, 2014), dan karekteristik limbah abu batu bara dapat digunakan sebagai penetral pH tanah dan menurunkan keasaman tanah (Hermawan et al, 2014). Abu dasar dapat meningkatkan kapasitas tukar kation, sehingga digunakan sebagai amelioran yang tidak merusak struktur tanah, tanaman, lingkungan, meningkatkan kesediaan hara, dan sumber energi mikroorganisme (Agustini et al, 2017).…”
Section: Gambar 5 Berat Basah (Gram) Tanaman Tomat 90 Hstunclassified
“…Decreased levels of organic materials in Inceptisols will indirectly affect the availability of nutrients in the soil, hence fertilization is needed. The application of manure generally more of a improve nature soil, and reduce the negative impact in plant growth and production and application of cattle manure contributed to the increased of total N and available P in soil (Agustini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Cahyono et al (2019Cahyono et al ( , 2020aCahyono et al ( , 2020b) revealed that Ultisols in pineapple plantations in Central Lampung have a pH range of 3.97-4.76, low soil organic carbon, nutrient content, and high Al 3+ and Fe 3+ content. In response to soil degradation, ameliorants such as organic matter (Agustini et al, 2017;Suwardi, 2021), coal ash (Nurmegawati et al, 2019;Ilham et al, 2020;Rais et al, 2021), lignite (Ram et al, 2007), and lime (Havlin et al, 2017;Cahyono et al, 2019;Cahyono et al, 2020a) are commonly used. These ameliorants can improve the soil quality and productivity of Ultisols.…”
Section: Introductionmentioning
confidence: 99%